A Pilot study on correlation between Zinc and Magnesium serum concentrations and coronary slow flow phenomenon - Dastani, Mostafa; Mokhtari, Mitra; Khameneh Bagheri, Ramin; Hassanzadeh, Pirooz; Jannati Yazdan Abad, Mahdi; Mohammadpour, Amir Hooshang; Elyasi, Sepideh (Acta Biomedica Atenei Parmensis, 2021)
Background: The pathophysiology of slow flow includes microvascular disorders, endothelial dysfunction, subclinical atherosclerosis, inflammation and anatomical factors. The role of magnesium and zinc in the development of microvascular and endothelial dysfunctions as well as atherosclerosis has been proven in previous studies, and the mechanism of the development has been studied. The aim of current study was to evaluate the serum concentration of zinc and magnesium in patients with epicardial coronary artery slow flow.Design: 125 patients who referred to Ghaem Hospital in Mashhad were selected based on inclusion and exclusion criteria. Magnesium and Zinc levels were evaluated in patients. The plasma levels of studied elements were compared among the different groups and the rate of coronary artery slow flow was evaluated based on the TIMI score.Results: The results of present study indicated that the serum level of Magnesium in the studied groups did not show a significant correlation with rate of coronary artery slow flow (P> 0.05). Serum Zinc concentration was significantly different in the studied groups, which means serum Zinc level in patients without coronary artery occlusion and  without epicardial slow flow were significantly higher than other groups (P> 0.01).Conclusion: In the present study, no significant relationship was found between the serum level of zinc and magnesium with the intensity of coronary artery slow flow based on TIMI, and further studies seem to be needed to investigate this relationship.